Reasons for Patients Preferring Extraction over Root Canal Treatment in a Tertiary Care Hospital - Kharel, Smriti; Shrestha, Deepti; Roy, Deepak Kumar; Dahal, Sirjana; Bhattarai, Ankita (Nepal Journal of Health Sciences, 2024)
Introduction: Dental caries is a major global oral health issue, potentially progressing to irreversible pulpitis and causing substantial discomfort. Although advancements in materials, instruments and knowledge have improved the success rates of root canal procedures, some patients opt for tooth extraction instead of root canal treatment. This choice can result in tooth loss, necessitating costly prosthetic replacements.Objective: The objective of this study was to determine the reasons for patients choosing extraction over root canal treatment.Methods: A descriptive cross-sectional study was conducted among 205 patients visiting the Department of Conservative Dentistry and Endodontics at Kathmandu Medical College for the treatment of irreversible pulpitis, who ultimately opted for extraction. A structured questionnaire was utilized, and responses were recorded and analyzed using the Statistical Package for the Social Sciences. Mean, standard deviation, frequency and percentage were calculated depending upon the nature of data.Results: The study found that the primary reason for patients not undergoing root canal treatment (RCT) was the high cost of RCT and crown, accounting for 42.9% (88 patients), followed by the need for more appointments with pain, at 31.2% (64 patients).Conclusions: This study revealed the cost of RCT and crown to be the major factor for patients opting out from RCT. The study provides valuable insights into the psychology of patients regarding RCT, highlighting reasons for its rejection. Such understanding assists dentists and specialists in tailoring treatment plans that align with patient preferences and needs.